Cybersecurity Strategies and Best Practices : A comprehensive guide to mastering enterprise cyber defense tactics and techniques - Aslaner, Milad (Packt Publishing Ltd., 2024)
This book is for security professionals and decision makers tasked with evaluating and selecting cybersecurity solutions to protect their organization from evolving threats. While a foundational understanding of cybersecurity is beneficial, it’s not a prerequisite.